Influence of the mold and heat treatment on the properties of bronze-aluminum - Dionicio Padilla, Eusebio (2004)
The influence of the moisture and sodium bentonite in the qualite moulding was tested; however one of the mixes was much better, which is the following: Sodium bentonite 7%, Water 4%, Silica sand 87%, ( AFS grain fineness 52). The physical properties of the molding sand was:permeability 235, green compresion, lb/in2 13,1. Cast nickel aluminium bronce Cu3 was tested: Tensile strength, kg/mm2 88,13, Yield strength, kg/mm2 28,3, Elongation in 2 inch, % 10, Metallography: etchant, amonium persulfate. Showing light a phase, eutectoide a + g2 and k phase.